Using GIS to Evaluate a Fire Safety Program in North Carolina. - Dudley, Thomas; Creppage, Kathleen; Shanahan, Meghan; Proescholdbell, Scott (Journal of Community Health, 2013)
Evaluating program impact is a critical aspect of public health. Utilizing Geographic Information Systems (GIS) is a novel way to evaluate programs which try to reduce residential fire injuries and deaths. The purpose of this study is to demonstrate the application of GIS within the evaluation of a smoke alarm installation program in North Carolina. This approach incorporates national fire incident data which, when linked with program data, provides a clear depiction of the 10 years impact of the Get Alarmed, NC! program and estimates the number of potential lives saved. We overlapped Get Alarmed, NC! program installation data with national information on fires using GIS to identify homes that experienced a fire after an alarm was installed and calculated potential lives saved based on program documentation and average housing occupancy. We found that using GIS was an efficient and quick way to match addresses from two distinct sources. From this approach we estimated that between 221 and 384 residents were potentially saved due to alarms installed in their homes by Get Alarmed, NC!. Compared with other program evaluations that require intensive and costly participant telephone surveys and/or in-person interviews, the GIS approach is inexpensive, quick, and can easily analyze large disparate datasets. In addition, it can be used to help target the areas most at risk from the onset. These benefits suggest that by incorporating previously unutilized data, the GIS approach has the potential for broader applications within public health program evaluation.